PENGARUH PENGGUNAAN MEDIA AMPAS KELAPA TERHADAP KEMAMPUAN MENGENAL WARNA ANAK USIA 3-4 TAHUN DI PAUD PERMATA BUNDA MUARO JAMBI - Fadilah Istiqomah; Kasmiati; Rizki Surya Amanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Color recognition is a crucial aspect of cognitive development in early childhood, contributing to logical thinking, creativity, and visual classification. However, initial observations at PAUD Permata Bunda Muaro Jambi revealed that children aged 3–4 years demonstrated low color recognition skills, which were suspected to result from monotonous and non-exploratory learning methods. This study aims to examine the effect of using coconut pulp media on improving color recognition skills in early childhood. This research employed a quantitative approach with a one-group pretest-posttest design. The sample consisted of 13 children aged 3–4 years, selected through total sampling. The research instrument was an observation sheet based on indicators of primary and secondary color recognition. Data were analyzed using paired sample t-test assisted by SPSS software. The results showed an increase in the average score from 16.92 (pretest) to 27.69 (posttest). The t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant effect of using coconut pulp media on children's color recognition skills. This media provided a multisensory, enjoyable, and contextual learning experience aligned with the developmental characteristics of early childhood. This study provides practical contributions for educators in designing learning activities based on natural materials and serves as a foundation for further research on other developmental aspects in early childhood.